1982
DOI: 10.1093/ptj/62.7.965
|View full text |Cite
|
Sign up to set email alerts
|

Two-Point Discrimination Assessment in the Upper Limb in Young Adult Men and Women

Abstract: Two-point discrimination sensitivity in the upper limb was evaluated in a sample of healthy, young adult men and women. A commercially available compass-type instrument was used to determine limits of two-point discrimination sensitivity in 11 skin areas on the subject's dominant side. For dermatomal regions of the arm and forearm, mean values ranged from 30.7 mm to 45.4 mm. In the hand, the skin overlying the first dorsal interosseous muscle demonstrated discrimination values of 21.0 mm while that covering th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
70
1
5

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 14 publications
8
70
1
5
Order By: Relevance
“…But highly specialized function like language is represented unilaterally on left side of cerebral hemisphere in 90-92% of human population. 10 Vision is most important sensory modality for perceiving written language and studies have shown that at least for its language related function; vision does show lateralization. Split visual field stimulation proved advantage of reading with right visual field (RVF) over left in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But highly specialized function like language is represented unilaterally on left side of cerebral hemisphere in 90-92% of human population. 10 Vision is most important sensory modality for perceiving written language and studies have shown that at least for its language related function; vision does show lateralization. Split visual field stimulation proved advantage of reading with right visual field (RVF) over left in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…2PD test was done in all 10 fingers of hand using weber compass. A standard procedure was followed while assessing participants using 2pd.…”
Section: Methodsmentioning
confidence: 99%
“…The normative value for the inter-point distance in this region is 2.6 mm. 34,35 Manual muscle testing found that the second finger flexor digitorum superficialis and profundus (FDS and FDP) strength diminished on the left compared to the right. Joint mobility tests (distraction, anterior, and posterior glide) were minimally restricted on the left compared to the right second finger PIP joint (left 2/65slight decreased movement; right 3/65normal).…”
Section: Examinationmentioning
confidence: 99%
“…Inter-point discrimination varies depending on which parts of the hand are being tested. Greatest sensitivity is reported on the volar surfaces of the thumb and first finger [92]. Although there is some variability between individuals, observations have been made that the smallest detectable distance between two points, applied simultaneously in this region, is approximately 1.88 mm [62] although this value increases with age [22].…”
Section: Spatial Resolutionmentioning
confidence: 99%